Development of a medical reminder app to promote medical adherence - Kaalim, Padayao John Carlo (Nanyang Technological University, 2024)
The Objective of this Project is to develop a Mobile Application that would help boost medical adherence to its users. This is done by monitoring the user’s medication and health supplement intake as well as storing historical data. Moreover, reminders in the form of notifications will be used to remind the users to take their respective medicines. Furthermore, the application would allow the user to search through the various medications that have taken to cross-reference with any symptoms they are currently experiencing. This Report focuses on the design and development process of the Medical Reminder Application. The Importance of this application is due to the need for stricter medical adherence for harsher illnesses as well as the difficulty of managing numerous medicines simultaneously. This application aims to provide easier medication tracking for users to follow medicine dosage regimens. The Mobile Application is developed in Android Studio, a development environment that is dedicated to developing Applications for Android Devices. The data entered into this application will be stored in a cloud database called “Cloud Firestore”, a database service provided by Google Cloud Platform, which allows the storage and querying of data in the form of collection and documents.